The impact of diurnal surface water fluctuations on groundwater diffusion: assessment through Fick's second law - Riazi, Amin; Turker, Umut; Rakhshandehroo, Gholam Reza (Springer Heidelberg, 2021)
This article reports the interaction between groundwater and surface water sources based on diurnal head fluctuations. The model uses the well-known Fick's second law to numerically estimate the pressure head variations in heterogeneous aquifers. The developed numerical model can examine the effects of both stream level sudden diurnal and gradual variations on the pressure heads in a confined heterogeneous aquifer. Calculations of pressure heads as a result of the interaction indicated that independent of the sequence of diffusion coefficient in the two similar confined aquifers, variations in pressure head will be the same at considerable amount of distances from the interaction region, unless when the total effective diffusion lengths are different. In the investigated cases, through time, the significant difference in the pressure heads between the gradual and sudden increase in stream water levels vanished, and the pressure head variations between the two cases became negligible.
Keywords: Confined aquifers; Diffusion; Groundwater flow; Head propagation; Numerical simulation; Stream head